Multi- objective optimization of switched reluctance motor drive in electric vehicles. (August 2018) - Gao, Xudong; Na, Risha; Jia, Chengyu; Wang, Xudong; Zhou, Yongqin
Abstract: Switched reluctance drive (SRD) has become one of the best choices for electric vehicle drive because it exhibits prominent advantages over other kinds of electric drive system. In this paper, the effects of load torque, turn-on and turn-off angle on the torque ripple and electric efficiency of the SRD are thoroughly analyzed based on the nonlinear dynamic model of switched reluctance motor (SRM). To reduce the torque ripple and improve the electric efficiency, a novel double-index synchronous optimization policy is proposed. Under different load torques and speeds, the model of adjustable turn-on and turn-off angle is established using the proposed optimization policy. Compared with conventional optimization strategies, the proposed method is verified to be effective for torque ripple suppression and electric efficiency improvement of the SRD simultaneously.